Combining omics technologies with CRISPR-based genome editing to study food microbes. (February 2020) - Pan, Meichen; Barrangou, Rodolphe
Abstract : The implementation of omics technologies such as genomics, proteomics and transcriptomics has revolutionized our understanding of microbiomes, and shed light on the functional attributes and mechanisms of action underlying the ability of probiotics to impact host health and starter cultures to drive food fermentation. Recently, molecular machines from CRISPR-Cas systems have redefined the gene editing toolbox and democritized our ability to alter the genome of food microorganisms. An integrated approach in which CRISPR-based genome editing is informed by omics studies is poised to enable the engineering of microorganisms and the formulation of microbiomes impacting the food supply chain. Here, we highlight the current applications of omics technologies in food microorganisms and CRISPR-based genome editing technologies in bacteria, and discuss how this integrated approach enables effective engineering of food microbes to generate enhanced probiotic strains, develop novel biotherapeutics and alter microbial communities in food matrices.